Kebijakan Dividen Sebagai Variabel Pemediasi Antara Pengaruh Umur Perusahaan, Ukuran Perusahaan, Dan Profitabilitas Terhadap Nilai Perusahaan - Kharisma Ayuning Putri; Saiful Anwar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The aim of this study is to analyse the abilty of dividend value as an intervening variable within the effect of firm age, firm size, and profitability on the firm value The data collection process is carried out through purposive sampling technique against manufacturing companies listed on IDX during 2016-2020. Based on the purposive sampling technique, 30 companies obtained for 5 years of observations that produced 150 observational data. Secondary data in the form of company’s annual report is used in this study. The type of research used is quantitative research with Microsoft Excel and SmartPLS 3.2.9 for windows as data processors. The analysis process used are construct validity test, reliability test, R-Square test, effect size test, and hypothesis testing. This study provides results that firm age does’nt affect the firm value, firm size doesn’t affect the firm value, profitabily has positive and significant effect on the firm value, firm age doesn’t affect the dividend policy, firm size doesn’t affect the dividend policy, profitability has positive and significant on the dividend policy, and dividend policy failed to mediate firm age, firm size, and profitability on the firm value. Keywords : Firm Age, Firm Size, Profitability, Dividend Policy, Firm Value